2021
DOI: 10.1093/oep/gpab008
|View full text |Cite
|
Sign up to set email alerts
|

Slow real wage growth during the Industrial Revolution: productivity paradox or pro-rich growth?

Abstract: I examine the implications of technological change for productivity, real wages and factor shares during the industrial revolution using recently available data. This shows that real GDP per worker grew faster than real consumption earnings but labour’s share of national income changed little as real product wages grew at a similar rate to labour productivity in the medium term. The period saw modest total factor productivity growth which limited the growth both of real wages and of labour productivity. Econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The nominal labor share measures the percentage of the wage bill on total return to factors, while the real labor share is the percentage of the total purchasing power of the population which accrues to workers. The two measures diverge if the ratio P w / P y changes relative to the base year: ceteris paribus (i.e., for the same distribution of nominal income) an increase in the prices of wage goods lowers the workers’ share on the total potential consumption—i.e., increases real inequality (Crafts, 2020; Geloso and Lindert, 2020). In this perspective, our framework is consistent with the suggestion to use group‐specific price indexes to deflate nominal income for estimating trends in inequality (Hoffman et al ., 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nominal labor share measures the percentage of the wage bill on total return to factors, while the real labor share is the percentage of the total purchasing power of the population which accrues to workers. The two measures diverge if the ratio P w / P y changes relative to the base year: ceteris paribus (i.e., for the same distribution of nominal income) an increase in the prices of wage goods lowers the workers’ share on the total potential consumption—i.e., increases real inequality (Crafts, 2020; Geloso and Lindert, 2020). In this perspective, our framework is consistent with the suggestion to use group‐specific price indexes to deflate nominal income for estimating trends in inequality (Hoffman et al ., 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 (right panel) plots two additional series of labor share since the late 18th century by Allen (2009b) and by Crafts (2020), and the four benchmark estimates of labor shares elaborated from social tables by Allen (2019). All series, including ours, find a clear worsening of inequality during the early stages of the Industrial Revolution—the “Engels’ pause” of the title of Allen’s (2009b) famous article.…”
Section: The Labor Share In Englandmentioning
confidence: 99%
“…Put differently, they say that demography, rather than mechanization or Marxist exploitation, undermined the scope for the industrial revolution to raise real wages. This is a valuable insight, especially given that recent research has found that the hallmark of that view, namely a declining share of labour in national income, is not observed in the data (Crafts, 2021). While Acemoglu and Restrepo (2019) have demonstrated that laboursaving technological progress can have an adverse effect on workers' living standards, the British industrial revolution is not an example of this outcome.…”
mentioning
confidence: 96%